On the apparent antagonism between feminist and mainstream metaphysics - Mikkola, M (Springer Verlag, 2016)
The relationship between feminism and metaphysics has historically been strained. Metaphysics has until recently remained dismissive of feminist insights, and many feminist philosophers have been deeply skeptical about any value that metaphysics might have when thinking about advancing gender justice. Nevertheless, feminist philosophers have in recent years increasingly taken up explicitly metaphysical investigations. Such feminist investigations have expanded the scope of metaphysics in holding that metaphysical tools can help advance debates on topics outside of traditional metaphysical inquiry (e.g. the nature of gender, sex, or sexuality). Moreover, feminist philosophers typically bring new methodological insights to bear on traditional ways of doing philosophy. Feminist metaphysicians have also recently begun interrogating the methods of metaphysics and they have raised questions about what metaphysics as a discipline is in the business of doing. In discussing such methodological issues, Elizabeth Barnes has recently argued that some prevalent conceptions of metaphysics rule out feminist metaphysics from the start and render it impossible. This is bad news for self-proclaimed feminist metaphysicians in suggesting that they are mistaken about the metaphysical status of their work. With this worry in mind, the paper asks: how does feminist metaphysics fare relative to ‘mainstream’ metaphysics? More specifically, it explores how feminist and ‘mainstream’ debates intersect, on what grounds do they come apart (if at all), and whether feminist metaphysics qualifies as metaphysics ‘proper’.